Representasi Nilai Perjuangan Keluarga dalam Mencapai American Dream pada Film Drama Minari - Ariningrum, Pramita (Hiski Malang, 2021)
The basic principle of the American Dream as an opportunity for every individual to generate wealth and start a new beginning is widely discussed in a film. American Dream in Minari departs from struggles of Asian immigrant families in achieving the standard of success in America. The purpose of this study is to describe the meaning and value of family struggles concerning the process of achieving the American Dream in the scene contained in one of the drama films from the United States entitled Minari as a representation of human life. This study uses a qualitative descriptive approach that is interpretive. Data collection techniques in the form of observation, documentation and literature study of each scene/ shot from the film Minari. The data validity technique in this study is in the form of data triangulation. In determining the theory and analysis techniques used critical paradigm. The data analysis technique used is the semiotic analysis of Charles Sander Pierce. The results of this study will show how immigrants from the point of view of Asian families struggle for their lives in the United States.